PENGARUH PENGHASILAN, TUNJANGAN SERTIFIKASI DAN MASA KERJA DOSEN TERHADAP KEINGINAN MENABUNG TABUNGAN HAJI DI KOTA PALEMBANG - Melia Frastuti (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
Doing the pilgrimage is a human obligation to Allah the almighty for people who can travel to Baitullah. People with limited funds and many other needs that must be met must rise and collect money before doing the pilgrimage. But there is an easy way to get around the pilgrimage payments that are of great value. Hajj savings is the answer. Opening hajj savings can make the payment of pilgrimage by way of setting aside some money for the preparation f doing the pilgrimage. The portion number is also a queue number for the departure of the Hajj which is listed on the first deposit of the cost of Hajj. Data analysis used to test the hypothesis using multiple linear regression analysis. Data collected by distributing questionnaires at three private universities in Palembang. Researcher disseminates specially to lecturers who already have cetification allowance. The result of the research concludes that income, certification allowance and the working period of lecturer have an effect to the desire to save hajj savings in Palembang. Keywords: income, cetification allowance, employment and saving